Contaminação por micotoxinas, resíduos de organofosforados e carbamatos : influências na qualidade do leite. - Ramos, Carlos Eduardo Crispim de Oliveira (2011)
Aiming to evaluate the milk contamination in the DPS for mycotoxins and chemical residues of organophosphates and carbamates it was made a study encompassing 95 SPL in three regions of Parana state. There where collected samples of milk, water and food and they were evaluated for chemical residues in all samples and aflatoxin only for food and milk. Mycotoxins in food (aflatoxin B1, B2, G1, G2, zearalenone and ochratoxin ) were detected by the method of thin layer chromatography - TLC and for the determination of aflatoxin M1 was used an immunoassay kit competitive ELISA Ridascreen®. The residues of organophosphates and carbamates was performed by colorimetric method qualitatively. There were evaluated the differences between regions, periods and the sources of mycotoxin contamination. Carbamates and organophosphates were screened for their presence in milk and the sources of food and water. Then it was estimated the contributions of each mycotoxin for milk contamination, as well as their respective contaminated food. Differences were found between periods (p < 0.05) for milk contamination with aflatoxin M1. For carbamates and organophosphates were found a different contamination sources (p < 0.01), and for the first pesticides used to parasitic herd control and for other pesticides used in agriculture. For food sources contamination resulting in the AFM1 contamination it was detected that AFB1 was the main source for the first. The AFG1 showed a strong correlation (p < 0.01) with AFB1 levels suggesting a causal relationship is a function of fungal strains producing both at the same time. It was also found the prevalence of aflatoxin contamination in 70% of contaminated samples and its predominant presence in relation to others in all kinds of foods analyzed. By identifying the checkpoints of contamination we can propose the inclusion of practical management methods to avoid this.